Certain Tamil Film Songs Belong to Yester Year Actors Such as Thyagaraja Bagavathar, N.S. Krishnan, Chandra Babu, Gemini Ganesan, Asokan, Nagesh, Jaishankar and Muthuraman Contains Ethical Imports that can be Compared with Ethical Theories - A Retrospective Reflection (Global Journal of Human-Social Science, 2025)
This research work is being undertaken to find out whether cetain film